Risk of Brownfield during Construction Stage: Case Study of PLTGU Project in Indonesia - Nasrudin Rozaq; Jati Utomo Dwi Hatmoko; Ferry Hermawan (Ridwan Institute, 2022)
Projects at the brownfield location cannot be separated from potential hazards related to geotechnical conditions and the existing project site. The construction phase is carried out at a location in the middle of an already operating factory. Lack of understanding of site characteristics and minimal use of the technology used can result in the project not meeting what was expected. This study aims to identify brownfield risk events during the construction phase of the PLTGU project development in Indonesia. This research uses quantitative and qualitative methods with a case study approach. Primary data were collected using documentation, field observations, survey questionnaires and structured interviews. The results of the study identified 23 (twenty three) and 6 (six) main risks based on the rankings, namely: 1) Groundwater level risk, 2) Location infrastructure damage, 3) Flood risk, 4) Structural damage and structural settlement, 5) Land subsidence, 6) Leakage of existing underground pipes. risks affecting project performance during the construction phase. The results of the study reveal that these risk events are risks that must be managed by project management during the construction phase.